Libertarianism Aspects as Reflected in “Dallas Buyers Club” Film - Finasari, Finasari (LANTERN (Journal on English Language, Culture and Literature), 2016)
AbstractThis thesis focuses on Libertarianism aspects as reflected in the characters ofDallas Buyers Club (2013) film by Jean-Marc Vallée. Dallas Buyers Clubfilm describes a reflection of libertarian movement or individual liberty with the limited intervention from the government by the characters named Ron Woodroof and Dr. Eve. The aim of this thesis is to describe libertarianism aspects in the movie by analyzing the intrinsic and extrinsic aspects. The writer employs library research to support the data with the film as the main data and some relevant books, journals, articles, and online documents and websites as the supporting data. To analyze the intrinsic aspects, the writer uses some theories of narrative elements and cinematography elements. To analyze the extrinsic aspects, the writer applies the theory of libertarianism with its key concepts by David Boaz. The result of this thesis proves that, based on David Boaz’s theory, the characters of the movie, such as Ron Woodroof has applied individual rights, free market, and limited government and Dr. Eve has applied spontaneous order as the basic key concepts of libertarianism.